PENGARUH PRICE EARNINGS RATIO, PROFITABILITAS, DAN NILAI PERUSAHAAN PADA RETURN SAHAM INDEKS LQ45 - Ryadi, Putu Rendi Suryagung; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
ABSTRACT This research saw the effect of the company fundamental information such as price earnings ratio, profitability, and firm value on LQ45 stock return with two control variables added which are firm size and type of industries to avoid biased result. This research use secondary data which is quantitative, using purposive sampling to get the data samples with 64 samples as results, and applied the uji asumsi klasik test, t-test, f-test, with multilinear regression technique. The results showed that the model is fit based on f-test, same thing on t-test, the results showed that all independent variables took effect on dependent variable in partial ways. Price earnings ratio has negative effect on stock return, profitability has negative effect on stock return, and firm value has positive effect on stock return. Therefore investor and rookie investor should see the price earnings ratio, profitability, and firm size to analyze the firm’s stock return.
Keywords: Price earnings ratio, profitability, firm value, stock return